Two-step controllable preparation of NiO nanocrystal anchored reduced graphene oxide sheets and their electrochemical performance as supercapacitors. (29th August 2017) - Gui, Jun; Zhang, Jinhua; Liu, Tianbao; Peng, Yanfen; Chang, Jie
Abstract : A feasible and expandable way to prepare homogenous NiO nanocrystal coated reduced graphene oxide (rGO-NiO) for high performance supercapacitor electrodes. Abstract : A feasible and expandable two-step strategy for the preparation of reduced graphene oxide (rGO) supported NiO nanocrystals (rGO-NiO) was developed using graphene oxide (GO), nickel sulfate and ammonia as raw materials. The rGO-NiO composites were obtained with the benefit of electrostatic attraction between GO and Ni 2+ (or Ni(OH)2 ) in a mild solution phase precipitation process and a sequent simultaneous thermal decomposition of Ni(OH)2 and reduction of GO in Ar. The influence of calcination temperature on the morphology, structure and electrochemical performance of the composites was investigated. The results show that the calcination temperature has less impact on the morphology of the composites. Homogenous cubic NiO nanocrystals (<10 nm) were well coated onto the surface of rGO both at 250 °C and 300 °C. However, the composites obtained at 300 °C (rGO-NiO 300) possess better crystallinity of NiO and a higher reduction degree of GO but lower specific surface area as well as pore volume compared with the composites achieved at 250 °C (rGO-NiO 250). rGO-NiO 250 is superior to rGO-NiO 300 in specific capacitance at all current densities (1044 vs. 422 F g −1 at 1 A g −1 and 600 vs. 360 F g −1 at 20 A g −1 ), but shows inferior rate capability (57.4% vs. 85.3% from 1 to 20 A g −1 ) and cycling stability (83% vs. 137% after 2000 cycles).